Feasibility of Remote Performance Assessment Using the Free Research Executive Evaluation Test Battery in Adolescents - Segura, Isis Angelica; Pompéia, Sabine (Frontiers in Psychology, 2021)
Lockdowns and other preventive measures taken to curb the spread of diseases such as COVID-19 have restricted the use of face-to-face cognitive assessment. Remote testing may be an alternative, but it should first be shown to be comparable to in-person assessment before being used more widely, during and after pandemics. Our aim was to evaluate the suitability of online, examiner-mediated administration of an open-access battery of executive function tests (the Free Research Executive Evaluation battery, or FREE) that may be adapted for various characteristics of diverse populations and used worldwide. A total of 96 9- to 15-year-olds (42 girls) were tested, half of whom online through video calls mediated by an examiner. Their performance was compared to that of the other 48 individuals tested face-to-face, who were matched against the online-tested participants for age, pubertal status, sex and parental schooling. The battery consists of two tests of the following executive domains: Updating (2-Back and Number Memory tests), Inhibition (Stroop Victoria and Stroop Happy-Sad) and Switching (Color Shape and Category Switch). Answers were vocal and self-paced, and the examiner recorded accuracy and time taken to complete in-person or online tasks. Free software only was used. Executive performance (e.g. executive costs, deducting vocal/psychomotor response times) did not differ statistically between online and in-person participants, thus showing that the FREE test battery holds promise for online cognitive assessment, pending confirmation from different samples and further validation studies.